Marsdenia tenacissima extract promotes gefitinib accumulation in tumor tissues of lung cancer xenograft mice via inhibiting ABCG2 activity. (12th June 2020) - Zhao, Can; Hao, Huifeng; Zhao, Haiyu; Ren, Wei; Jiao, Yanna; An, Guo; Sun, Hong; Han, Shuyan; Li, Pingping
Abstract: Ethnopharmacological relevance: Marsdenia tenacissima extract (MTE) is the water-soluble part of a traditional Chinese medicine Marsdenia tenacissima (Roxb.) Wight & Arn, and is commercially available in China for treating cancers. MTE has been revealed to be effective in improving gefitinib efficacy in treating non-small cell lung cancer (NSCLC). However, the mechanisms remain to be defined. Aim of the study: To determine the effects of MTE on gefitinib metabolism and accumulation in vivo, and to explore the underlying mechanisms. Materials and methods: MTE or vehicle were intraperitoneally administrated to the H1975 xenograft model, followed by intragastric administration of gefitinib 12 h later. Mice plasma, tumors and liver tissues were harvested for further analysis. Hoechst 33342, a specific substrate of ATP Binding Cassette Subfamily G Member 2 (ABCG2), was used to determine the effects of MTE on activities of ABCG2 in tumor cells. Results: A higher concentration of plasma gefitinib was detected in MTE-treated mice at 24 h after delivery of gefitinib, however, it became insignificant in another 24 h. By contrast, gefitinib levels were continuously higher in MTE-pretreated mice tumor tissues at 12–48 h post gefitinib administration. MTE suppressed plasma levels of gefitinib metabolites (M523595, M608236 and M537194) in the first 24 h after gefitinib delivery, and inhibited activities of liver CYP2D6 and CYP3A4 at early stage (within 6 h) after gefitinib treatment. Strikingly, the activities of ABCG2, the primary drug transporter for gefitinib, were significantly inhibited by MTE in H1975 lung cancer cells. Further, it was identified that tenacissoside H, but not tenacissoside I, may contribute to the ABCG2-suppressive effects of MTE. Conclusions: MTE pretreatment temporarily elevated plasma concentrations of gefitinib via inhibiting CYP450 enzymes. Most importantly, MTE promoted gefitinib accumulation in tumor tissues in a long-lasting manner via decreasing activities of ABCG2, a drug transporter responsible for gefitinib efflux. Graphical abstract: Image 1 Highlights: MTE-pretreatment elevated plasma levels of gefitinib in a temporary manner. MTE-pretreatment promotes gefitinib accumulation in tumors in a long-lasting manner. MTE reversibly inhibits liver CYPs, especially CYP2D6 and CYP3A4. MTE suppresses activities of ABCG2 which is responsible for gefitinb efflux. Tenacissoside H, a constitute of MTE, inhibits ABCG2 activities.